Pengaruh Harga dan Citra Merek Terhadap Keputusan Pembelian Handphone Vivo Sirvei di Perumahan Griya - Basuki Rahmat (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Consumers will make purchasing decisions about a product influenced by several things, namely, price and consumers can make purchasing decisions. This is the company's main goal in making a profit. Apart from price, what influences purchasing decisions is brand image, where brand image plays an important role in a decision to purchase a Vivo cellphone. The formulation of the problem in this research is 1. Does price influence the decision to purchase Vivo cellphones at Griya Satria Cibeber Housing, 2. Does brand image influence the decision to purchase Vivo cellphones at Griya Satria Cibeber Housing, 3. Do price and brand image influence purchasing decisions Vivo cellphone at Griya Satria Cibeber Housing Complex. This research aims to find out how influential price and brand image are on purchasing decisions for Vivo cellphones. The analysis method used is quantitative descriptive analysis and uses a survey method of 60 respondents. The data collection technique uses an instrument in the form of a questionnaire. Data analysis uses classical assumption tests, multiple linear regression and coefficient of determination analysis. Based on the results of the hypothesis test, the value tcount > ttable (3,455 > 2,542) and the significant value 0.001 < ɑ (0.05), then H0 is rejected and Ha is accepted. Based on the significance test, it was found that there is a significant influence between the price variable (X1) on purchasing decisions (Y). And the value of tcount > ttable (4,593 > 2,542) and the significant value is 0.000 < ɑ (0.05), then H0 is rejected and Ha is accepted. Based on the significance test, it was found that there is a significant influence between the brand image variable (X2) on purchasing decisions (Y).